Pulmonary Eosinophils at the Center of the Allergic Space-Time Continuum - Schetters, Sjoerd T. T.; Schuijs, Martijn J. (Frontiers in Immunology, 2021)
Eosinophils are typically a minority population of circulating granulocytes being released from the bone-marrow as terminally differentiated cells. Besides their function in the defense against parasites and in promoting allergic airway inflammation, regulatory functions have now been attributed to eosinophils in various organs. Although eosinophils are involved in the inflammatory response to allergens, it remains unclear whether they are drivers of the asthma pathology or merely recruited effector cells. Recent findings highlight the homeostatic and pro-resolving capacity of eosinophils and raise the question at what point in time their function is regulated. Similarly, eosinophils from different physical locations display phenotypic and functional diversity. However, it remains unclear whether eosinophil plasticity remains as they develop and travel from the bone marrow to the tissue, in homeostasis or during inflammation. In the tissue, eosinophils of different ages and origin along the inflammatory trajectory may exhibit functional diversity as circumstances change. Herein, we outline the inflammatory time line of allergic airway inflammation from acute, late, adaptive to chronic processes. We summarize the function of the eosinophils in regards to their resident localization and time of recruitment to the lung, in all stages of the inflammatory response. In all, we argue that immunological differences in eosinophils are a function of time and space as the allergic inflammatory response is initiated and resolved.